Were California’s Decarceration Efforts Smart? A Quasi-Experimental Examination of Racial, Ethnic, and Gender Disparities - Gottlieb, Aaron (Criminal justice and behavior, 2021)
Over the last decade, California has undertaken one of the largest criminal justice reform efforts in recent U.S. history. However, little is known about the causal impact of these reforms on the overall incarceration rate and disparities in incarceration rates across demographic subgroups. Using a quasi-experimental synthetic control method and data from the Vera Institute of Justice and the U.S. Census Bureau, our results provide strong evidence that California’s reforms have substantially reduced the state’s overall incarceration rate, but that they have resulted in an increase in Latinx-White incarceration disparities. We also find suggestive evidence that the reforms have exacerbated Black-White incarceration disparities and disparities between men and women. Our study is especially relevant at a time when the United States is increasingly interested in reducing the population of people incarcerated and suggests that care must be taken to ensure that reform efforts do not increase incarceration disparities among demographic subgroups.